Tracked Changes. Plastics piping systems for water supply and for buried and above ground drainage, sewerage and irrigation under pressure. Oriented unplasticized poly(vinyl chloride) (PVC-O). Fittings Part 3, (27th February 2023) - British Standards Institution
No abstract available